Maize (Zea mays)-based intercropping systems with pulses under rainfed condition - Abbas, Mohd; Tomar, Surendra S; Nigam, K B (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during rainy season of 1990-91 and 1991-92 to find out the best legume intercrops with maize (Zea mays L.) with appropriate row combination for Vertisol of north-western Madhya Pradesh. ’H 405’ maize, ’J8 72- 44’ soybean [Glycine max(L.) Merr.], â€˜T 9’ blackgram (Phaseolus mungo L.) and ’ICPL 87’ pigeonpea [Cajanus cajan (L.) Millsp.J were tested in monoculture and intercropping systems with 3 ratios (2:2, 2:4 and 4:2). Maize + soybean was better than maize + blackgram combination for yield and competitive parameters. No significant difference was observed among maize + soybean ratios of 2:2, 2:4 and 4:2 for seed yield, biomass yield, maize-equivalent yield and landÂ equivalent ratio, but 2 : 2 ratio gave comparatively better monetary advantage and competitive parameters. Similar trend was observed for all maize + blackgram combinations except significant higher intercrop yield of black gram in 2: 4 combination. Maize + pigeonpea in 2:2 ratio gave better intercrop yield, biomass yield, maize-equivalent yield and monetary advantage than 4: 2 ratio. Maximum competitive ratio of 1.764 for maize was observed in maize + blackgram in 2 : 2 ratio, and among intercrops pigeonpea recorded 2.772 competitive ratio in maize + pigeonpea in 2: 4 ratio. Highest maize-equivalent yield of 6.115 tonnes/ha was recorded by pigeonpea, followed by soybean (5.453) and blackgram (3.341) compared with 3.220 tonnes/ha by maize. Maize was dominant to soybean and blackgram, whereas pigeonpea was dominant to maize in different cropping systems. In Venisol maize + pigeonpea in 2 : 2 ratio was more advantageous, as reflected by different yield, monetary advantage and competitive parameters, except maize-equivalent yield wh.ich was at par with sale pigeonpea crop.